Electrochemically polymerised composites of multi-walled carbon nanotubes and poly(vinylferrocene) and their use as modified electrodes: application to glucose sensing. - Sljukić, B; Banks, C; Salter, C; Crossley, A; Compton, R (2006)
We report electrochemical composites of multi-walled carbon nanotubes (MWCNTs) with poly(vinylferrocene) (PVF). The polymeric architecture is prepared by first immobilising the MWCNTs onto a glassy carbon substrate, which acts to introduce electrical current into the composite, with the MWCNTs acting as 'molecular wires'. PVF films of varying surface coverages can be obtained by simply controlling the time a constant potential of +0.7 V (vs. Ag) wire is applied; with the characteristics of the derivatised MWCNTs examined by cyclic voltammetry and scanning electron microscopy. The application of the composite for glucose determination in aqueous solutions was investigated using linear sweep voltammetry, where it was found that the composites supported on glassy carbon substrates are superior to bare glassy carbon electrodes polymerised with PVF, likely due to the comparatively higher number of electrocatalytic centres in the former. This protocol was successfully transferred to prepare a PVF-MWCNT-paste electrode which was applied to glucose detection in diluted laked horse blood. The obtained results show potential and promising practical application for the polymer-derivatised MWCNT-modified electrodes in amperometric sensors for glucose determination.